Deterioration of Glycemic Control Induced by Pentoxifylline and Cilostazol in a Diabetec Patient with Peripheral Vascular Disease - Durga V, Kanaka; DL, Britto; S, Shanmugapriya; T, Saravanan (Indian Journal of Pharmacy Practice)
A 67-year-old South Asian male with type 2 diabetes mellitus, hypertension and ischemic heart disease was admitted with dry gangrene of right leg second toe. Angiography of right lower limb revealed peripheral vascular disease. He received pentoxifylline 400mg twice a day and cilostazol 100mg twice a day for 6 days following disarticulation. During this period, there was a marked elevation of blood sugar requiring higher dosage of insulin. On withholding the offending drugs there was a definite fall in blood sugar indicating a positive dechallenge. An erroneous exposure of pentoxifylline occurred following which the glycemic control further deteriorated, suggestive of a positive rechallenge though it was unintentional. Pentoxifylline and Cilostazol might have induced hyperglycemia by favoring intestinal glucose absorption through increased cAMPlevels and GLUT2 expression necessitating management with higher dosage of insulin.
Keywords: Cilostazol; Diabetes mellitus; Hyperglycemia; Pentoxifylline